Differential accumulation patterns of microbial necromass induced by maize root vs. shoot residue addition in agricultural Alfisols. (January 2022) - Xu, Yingde; Gao, Xiaodan; Liu, Yalong; Li, Shuangyi; Liang, Chao; Lal, Rattan; Wang, Jingkuan
Abstract: Soil organic carbon (SOC) has significant implications in regulating soil health. Emerging insights emphasize the important role of microbial anabolism in SOC storage by continuously transforming plant fragments into persistent microbial residues. However, knowledge of the sequestration pathway of root versus shoot carbon (C) is under debate. While recent studies have shown that labile shoot residue is disproportionately important for stable SOC accumulation through microbial assimilation, how plant root vs . shoot residue retention impacts microbial-derived C under different soil fertility conditions remains elusive. Here, we conducted a 500-d in situ experiment using Alfisols with low fertility (LF) and high fertility (HF) amended with maize root or shoot (both stem and leaf) residues. The microbial residues (amino sugar biomarkers) and microbial communities (lipid biomarkers) were analyzed at 60, 90, 150, and 500 d after the amended materials were added. The results showed that shoot residue input facilitated microbial residue accumulation more efficiently than root input before 150 d. However, at the end of the experiment, the treatment containing added root residue accumulated more microbial residues and produced a higher proportion of microbial residue in SOC, compared with shoot treatment. These results provide novel evidence that root residue can also yield SOC efficiently through the organic substrate–microbial anabolism pathway, but it depends on the decomposition period. Moreover, soil fertility plays an important role in regulating the quantity and relative composition of microbial residues. Specifically, crop residue application greatly increased the contribution of microbial residue C to SOC in the LF treatment compared to that in the HF treatment on day 500. Meanwhile, crop residue addition had a more positive effect on fungal residue accumulation in the LF soil, while it facilitated the accumulation of bacterial residue in the HF soil. These findings highlight that crop residue addition (especially root residue) is an effective approach for improving microbial-derived C sequestration in infertile soils. Highlights: Microbial contribution to SOC was quantified by amino sugar and lipid biomarkers. Root residue is helpful to the microbial residue accumulation in the long-term scale. Crop residue addition promotes the fungal residue accumulation in the LF soil. Crop residue addition facilitates the bacterial residue accumulation in the HF soil. Crop residue addition is an effective way to improve SOC quality in infertile soils.